2007
DOI: 10.4161/cbt.6.3.3904
|View full text |Cite
|
Sign up to set email alerts
|

Palladin is overexpressed in the non-neoplastic stroma of infiltrating ductal adenocarcinomas of the pancreas, but is only rarely overexpressed in neoplastic cells

Abstract: Background: It has recently been suggested that overexpression of palladin in sporadic pancreatic cancer may contribute to pancreatic cancer's invasive and migratory abilities. This hypothesis was based on reverse transcriptase-polymerase chain reaction analyses of bulk pancreatic tissue, yet pancreatic cancer is a complex admixture of neoplastic epithelial cells and desmoplastic stroma.Design: Immunohistochemical labeling of tissue microarrays was used to define the patterns of palladin protein expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
38
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 25 publications
9
38
0
1
Order By: Relevance
“…Serial analysis of gene expression (SAGE) of pancreatic and colorectal cancers at invasive sites, comprising both epithelial and stromal elements, identified palladin to be within a cluster of invasion-specific genes (63). However, in a separate report by Salaria et al, it was found that palladin expression levels were comparable between pancreatic cancer cells and non-neoplastic pancreatic cells, with high expression levels predominantly seen in non-neoplastic stromal fibroblasts of pancreatic tumor sections (64). These previous reports showing an up-regulation of palladin with increased invasion is invariant to our observation that loss in palladin expression is associated with increased invasiveness in colon rectal cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Serial analysis of gene expression (SAGE) of pancreatic and colorectal cancers at invasive sites, comprising both epithelial and stromal elements, identified palladin to be within a cluster of invasion-specific genes (63). However, in a separate report by Salaria et al, it was found that palladin expression levels were comparable between pancreatic cancer cells and non-neoplastic pancreatic cells, with high expression levels predominantly seen in non-neoplastic stromal fibroblasts of pancreatic tumor sections (64). These previous reports showing an up-regulation of palladin with increased invasion is invariant to our observation that loss in palladin expression is associated with increased invasiveness in colon rectal cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, Brentnall et al have identified a germ line mutation in the PALLD gene on chromosome 4q32-34 in Family X, a family with a unusual phenotype of early-onset pancreatic insufficiency, diabetes mellitus, and familial pancreatic cancer typically before age 40 (12). This locus does not seem to be a site of linkage in most pancreatic cancer families (13,14), although additional mutational studies of PALLD in other kindreds are awaited (15).…”
mentioning
confidence: 99%
“…Stromal contamination and small samples are significant challenges when studying any pancreatic neoplasm (26). Careful laser capture microdissection (LCM) of neoplastic cells can prevent contamination by the abundant stromal reaction associated with the infiltrating cancer cells, and whole genome amplification (WGA) techniques can accurately copy small starting amounts of DNA, thereby enabling the detailed analysis of DNA available from LCM tissues (27).…”
mentioning
confidence: 99%
“…Les études des expressions des gènes montrent une surexpression de ce gène au cours de la carcinogenèse pancréatique [55]. Cependant, les études ultérieures n'ont pas confirmé l'implication de ce gène dans le cancer pancréa-tique familial [56][57][58][59][60].…”
Section: Gène Paladin (Palld)unclassified